PEMBERDAYAAN PEREMPUAN PAPUA UNTUK KEMAJUAN EKONOMI LOKAL - Lena Ratu Ningsih Kowarin; Fitriana Fitriana; Rachmat Agus Santoso (LP2M Universitas Bina Bangsa, 2024)
This research focuses on the Wamanggu market in Papua and the women's empowerment efforts in the vicinity, aiming to improve the progress of the local economy. The introduction explains that women's empowerment is the transformation of power relations in the family, society, market, and state. Women's empowerment is considered strategic to increase their role in development. In Papua, women face barriers such as gender inequality, local traditions, and social instability. Therefore, women's empowerment is not only achieving gender equality but also an integral strategy for the welfare of society. This study uses a qualitative approach with a case study method. Primary data was obtained through in-depth interviews with key informants, such as the Head of the Merauke Regency Bapenda and the Chairman of the Merauke Market Traders Association. Secondary data was obtained from literature studies and documents related to women's empowerment in the Warmanggu market. The results of the research are expected to provide an in-depth understanding of the role of women in the local economy, the obstacles faced, and the empowerment initiatives that already exist. The objectives of the research include analyzing the role of women, identifying obstacles, evaluating empowerment programs, and providing recommendations to improve women's empowerment in Papua. It is hoped that this research can make a positive contribution to local economic development, create an inclusive environment, and provide a gender perspective in sustainable development policies in Papua